B-1 cell-mediated modulation of M1 macrophage profile ameliorates microbicidal functions and disrupt the evasion mechanisms of Encephalitozoon cuniculi - Pereira, Adriano; Alvares-Saraiva, Anuska Marcelino; Konno, Fabiana Toshie de Camargo; Spadacci-Morena, Diva Denelle; Perez, Elizabeth Cristina; Mariano, Mario; Lallo, Maria Anete (PLOS Neglected Tropical Diseases, 2019)
Here, we have investigated the possible effect of B-1 cells on the activity of peritoneal macrophages in E. cuniculi infection. In the presence of B-1 cells, peritoneal macrophages had an M1 profile with showed increased phagocytic capacity and index, associated with the intense microbicidal activity and a higher percentage of apoptotic death. The absence of B-1 cells was associated with a predominance of the M2 macrophages, reduced phagocytic capacity and index and microbicidal activity, increased pro-inflammatory and anti-inflammatory cytokines production, and higher percentual of necrosis death. In addition, in the M2 macrophages, spore of phagocytic E. cuniculi with polar tubular extrusion was observed, which is an important mechanism of evasion of the immune response. The results showed the importance of B-1 cells in the modulation of macrophage function against E. cuniculi infection, increasing microbicidal activity, and reducing the fungal mechanisms involved in the evasion of the immune response.